Smart Tumbler / Nur Hidayah Jaafar, Mas Hanisah Azmi … [et al.] - Jaafar, Nur Hidayah; Azmi, Mas Hanisah; Fadzerun, Ain Madihah; Ahmar, Ahmad Hafizi (2018)
A newly product developed based on generated ideas and concerns to those in needs of change in the normal product. This product is the results for those who need to stay hydrated other than creating awareness of the importance of hydration status. The targeted population was those of athlete and the general population around the world. The specifications of this product are slender and long bottle, special alarm as a reminder to drink and as location detection, safety locked and available in many colors. Based on the variables of questionnaires and survey done, this new product was generated through those demands